Pengaruh Koordinasi pada Bagian Pemerintahan Desa terhadap Keberhasilan Pembangunan Desa di Kacamatan Watang Sidenreng Kabupaten Sidenreng Rappang - Dina Dina (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract The research was conducted at the District Office of Watang Sidenreng. The purpose of this research was to determine the effect of coordination on the part of village government to the success of rural development at Watang Sidenreng District in Sidenreng Rappang Regency, and the factors that influenced it. Data collection methods used were observation, literature study, and questionnaires. The population were 41 people, and all of them were accounted as sample. The results of the coordination effect was well at 87,80%. The coordination done by the village administration was also good at 90,24%. Vertical coordination which coordinated employees and the head of the village was good at 82,93%. Functional coordination performed by employees with village officials was good at 73,17%. Vertical coordination and functional coordination within the research was good at 78,05%. The elements contained in coordination efforts, in terms of resources’ utilization or the potential of the officials was good at 80,49%. The integrity and harmony in the execution of officials’ duties was good at 90,24%. Implementation of the government in terms of government affairs, political order, coordination, supervision and other government affairs was good at 92,88%. The education level of district office personnel and village office personnel was adequate at 87,80%. The effect of education level in coordinating the successful development of rural villages was good at 92,68%. The development done in Watang Sidenreng District was good at 60,98%. The participation of the community in executing village development was good at 80,49%. Factors affecting, namely a) contributory factor; the government’s attention and assistance through the PNPM program was strongly supportive at 60,98%, and b) inhibiting factor; the lack of human resources was strongly inhibit at 56,10%.